Current evidence on the adoption of indicator condition guided testing for HIV in western countries: A systematic review and meta-analysis. (May 2021) - Bogers, S.J.; Hulstein, S.H.; Schim van der Loeff, M.F.; de Bree, G.J.; Reiss, P.; van Bergen, J.E.A.M; Geerlings, S.E.; ,
Abstract: Background: Indicator condition (IC) guided testing for HIV is an effective way to identify undiagnosed people living with HIV, but studies suggest its implementation is lacking. This systematic review provides an overview of the adoption of IC-guided testing in Western countries. Methods: Seven ICs were selected: tuberculosis (TB), malignant lymphoma, hepatitis B, hepatitis C, cervical/vulvar carcinoma/intraepithelial neoplasia grade 2+ (CC/CIN2+, VC/VIN2+), and peripheral neuropathy (PN). Embase and Ovid MEDLINE were searched up to November 20th, 2020. Publications of all types, using data from ≥2009, reporting on HIV test ratios in patients ≥18 years in all settings in Western countries were eligible. HIV test ratios and positivity were reported per IC. A random effects-model for proportions was used to calculate estimated proportions (ES) with 95% CIs. This study was registered at PROSPERO, registration number CRD42020160243. Findings: Fifty-seven references, including 23 full-text articles and 34 other publications were included. Most (28/57) reported on HIV testing in TB. No reports on HIV testing in VC/VIN2+ or PN patients were eligible for inclusion. Large variation in HIV test ratios was observed between and within ICs, resulting from different testing approaches. Highest HIV test ratios (pooled ratio: 0·72, 95%CI 0·63–0·80) and positivity (0·05, 95% CI 0·03–0·06) were observed among TB patients, and lowest among CC/CIN2+ patients (pooled ES test ratio: 0·12, 95%CI 0·01–0·31, positivity: 0·00, 95%CI 0·00–0·00). Interpretation: IC-guided HIV testing is insufficiently implemented in Western countries. The large variation in test ratios provides insight into priority areas for implementing routine IC-guided HIV testing in the future. Funding: HIV Transmission Elimination in Amsterdam (H-TEAM) consortium and Aidsfonds (grant number P-42, 702).